2015
DOI: 10.3889/oamjms.2015.054
|View full text |Cite
|
Sign up to set email alerts
|

Association between Estrogen Receptor Alpha Gene Polymorphisms and Susceptibility to Idiopathic Scoliosis in Bulgarian Patients: A Case-Control Study

Abstract: BACKGROUND:The current consensus on idiopathic scoliosis maintains that it has a multifactorial etiology with genetic predisposing factors.AIM:Estrogen receptor alpha gene has been considered as candidate gene of idiopathic scoliosis.MATERIAL AND METHODS:We conducted a case-control study of Bulgarian population samples (eighty patients with idiopathic scoliosis and one hundred-sixty healthy unrelated gender-matched controls) trying to investigate the association between common genetic polymorphisms of estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This is possible because of the reactions analysis and postural strategies, which forms the basis of mechanisms that promote the body in balance (Saifi, Kang & Lehman, 2016). Balance is a certain state of postural system, which is characterized by the vertical orientation of the body achieved due to aligning the forces acting on a body and their moments (Nikolova et al 2015). The balance is provided by the nervous system through the reflex tension of respective muscle groups called anti-gravity muscles (Romano et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…This is possible because of the reactions analysis and postural strategies, which forms the basis of mechanisms that promote the body in balance (Saifi, Kang & Lehman, 2016). Balance is a certain state of postural system, which is characterized by the vertical orientation of the body achieved due to aligning the forces acting on a body and their moments (Nikolova et al 2015). The balance is provided by the nervous system through the reflex tension of respective muscle groups called anti-gravity muscles (Romano et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…ESR1 gene is expressed in both human bone cells( osteoclasts and osteoblasts) and its mutations were recognized as a causative factor for increased bone resorption and impaired skeletal growth. In 2015, a case-control study demonstrated that the ESR1 PvuII genetic polymorphism is associated with IS and curve severity in the Bulgarian population 13 . The vitamin D receptor (VDR) is defined as a ligand-activated transcription factor that controls gene expression in several cell types, including immune cells.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…As a well established AIS susceptibility gene in the Caucasian population, the CHL1 gene failed to be replicated in the Chinese Han population [ 26 ]. The ESR1 gene was firstly confirmed to be associated with AIS in the Japanese population and later successfully validated in the Chinese and the Caucasian population [ 13 , 14 , 27 , 28 ]. Interestingly, this association was not supported by other 3 replication studies separately performed in the Asian and the Caucasian population [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%